Research on Optimal Design of Pressure Relief Blasting Parameters of Middle Rock Pillar in Near Vertical Coal Seam. (29th May 2022) - Wang, Yadi; Yu, Shiqi; Rong, Hai; Pan, Liting
Abstract : In order to prevent the occurrence of rockburst accident caused by the stress concentration of the middle rock pillar in the near-vertical coal seam and affect the mining of the lower coal seam in the known goaf, taking Wudong coal mine in Xinjiang as an example, based on the special geological and mining conditions of the mine, through the simulation experiment and numerical analysis of similar materials, the variation law of the stress distribution of the middle rock pillar with the increase in mining depth is analyzed. A presplitting blasting pressure relief technology of drilling a construction chamber in the middle of the rock column is proposed to form a buffer layer in the rock wall and effectively prevent the continuous downward movement of stress. In order to achieve the optimal blasting effect, the finite element numerical simulation software GTS NX is used to carry out the chamber rock mass hole blasting simulation experiment, the three influencing factors of blasting effect, such as charge quantity, blast hole diameter, and blast hole row spacing, are comprehensively considered, and the optimal pressure relief blasting parameters with the radius of borehole blasting crack circle and the width of plastic zone as the index are determined. The experimental results show that under the condition of determining the physical and mechanical parameters of coal and rock, the blast hole diameter has become the main control factor affecting the blasting pressure relief effect, followed by the charge amount. Through 9 groups of orthogonal tests, the optimal combination of the three indexes is 6 kg charge, 150 mm hole diameter and 10 m hole row spacing. The practical engineering application results of the combination are tested by downhole transient electromagnetic detection (TEM), and it is found that the pressure relief effect is obvious. The preliminary conclusions of the study have guiding significance for the pressure relief and erosion prevention of the middle rock pillar in Wudong mine and provide experimental methods and theoretical basis for the determination of blasting pressure relief parameters in other mines.